2013
DOI: 10.12732/ijpam.v88i1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Determinant of an Interval Matrix Using Gaussian Elimination Method

Abstract: We introduce the notion of determinant and related results for interval matrices. We propose a Gaussian elimination like algorithm for computing the enclosures of the determinant of interval matrices. Numerical examples are also provided to show the efficiency of the proposed algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The system is evaluated by three mathematical formulations which were developed by Gauss, Krawski and Hansen (Nirmala et al, 2013;Hansen and Sengupta, 1981;Neumaier, 1999). To avoid possible rounding errors and divergent results, we propose to use an intersection method.…”
Section: Calculation Of Unknown Displacementsmentioning
confidence: 99%
“…The system is evaluated by three mathematical formulations which were developed by Gauss, Krawski and Hansen (Nirmala et al, 2013;Hansen and Sengupta, 1981;Neumaier, 1999). To avoid possible rounding errors and divergent results, we propose to use an intersection method.…”
Section: Calculation Of Unknown Displacementsmentioning
confidence: 99%
“…Ganesan and Veeramani (2005) developed an innovative collection of arithmetic operations for interval numbers with the overarching goal of mitigating disparities in a general context. Nirmala et al (2011) devised an inventive approach for calculating the inverse of an interval matrix, which subsequently proved to be a valuable tool for addressing interval-linear problems. Hartman et al (2021) introduced an algorithm for computing the spectral decomposition of an interval matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Ganesan and Veeramani(2005) offered some properties on interval matrices. Nirmala et al(2011) studied a new approach on inverse interval matrix. Sudha et al(2021) suggested a novel method for handling fixed charge transportation issues using interval parameters.…”
Section: Introductionmentioning
confidence: 99%